LITERATURE REVIEW : PENGARUH TEKNIK HYPNOBIRTHING TERHADAP INTENSITAS NYERI PADA IBU BERSALIN - Siantar, Rupdi lumban; Siregar, Renince; Oktaviani, Rokhma Herlita (Jurnal Ayurveda Medistra, 2021)
Many problems can occur due to labor pains that are not properly managed. Pain during labor is caused by uterine contractions which can result in increased activity of the sympathetic nervous system which can affect psychological conditions including the mother's perception of pain and anxiety during labor. Various methods are carried out as efforts to reduce labor pain, including non-pharmacological methods using the Hypnobirthing technique. This literature study aims to determine the effect of hypnobirthing techniques on pain intensity in labor mothers. Method : research method using literature study method. This study is a literature review, the source for conducting this literature includes search studies in the form of research journals totaling 10 journals. Using the 2015-2020 publication year. Choose journals according to scientific articles. Result : There is an influence between the use of hypnobirthing techniques on the intensity of pain in laboring mothers such as the reference journal that I took, which states that of the 30 research samples, 15 respondents who were given hypnobirthing as much as 60% experienced moderate pain, and 15 respondents who were not given hypnobirthing were 66.7% experiencing severe pain. Conclusion : Hypnobirthing techniques can affect the reduction of pain in laboring mothers.